ALOKASI BELANJA MODAL SEBAGAI PEMODERASI PENGARUH KINERJA KEUANGAN PADA PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI BALI - Sukarmi, Ni Wayan; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.03.TAHUN 2016, 2016)
Autonomy can be seen from the area of ??financial performance and the financial capacity of local governments. Good financial performance shows the financial management of local government more transparent and accountable. The purpose of this research is intended to note the role of the financial performance of local governments to the rate of increase in the economy by allocating interactions capital costs as a moderating variable. The research data source of reports on realization of local government finances se Bali Province the period 2009 to 2013 and a secondary data. The research hypothesis was tested by moderated regression analysis (MRA).Regression test results indicate the general moderation of expenditure allocation of financial performance modalmemperkuat influence on economic growth. In particular interaction capex strengthen the influence of the level of financial dependence and financial independence on economic growth. While the influence of decentralization, the effectiveness of local revenue (PAD) and the degree of contribution of the Regional Owned Enterprises (enterprises) to the interaction of economic growth capex showed no significant results. From the results of multiple linear regression test known that decentralization, financial dependence, the effectiveness of PAD, financial independence, and the contribution of enterprises have no effect on economic growth. Efforts to optimize financial management to improve the reception area should be improved. Increased revenue more effectively provide a stimulus for regional economic growth. The local government should have a standard to assess the level of success in the reception area and its use for the community.
Keywords: Financial Performance, Capital Expenditures, Economic Growth